Effects of an Autonomy-Supportive Physical Activity Program for Compensatory Care Students During Recess Time - Huéscar, Elisa; Moreno-Murcia, Juan Antonio; Domenech, Jose F.; Núñez, Juan L. (Frontiers in Psychology, 2020)
The purpose of this study was to examine the effects of a physical activity-based intervention conducted during recess time for Spanish students with special needs. The intervention was designed to utilize an autonomy-supportive motivational style to promote feelings of autonomy and to contribute to increased physical activity involvement in these students. Participants were 62 students in the fifth and sixth year of elementary school, with ages between 10 and 12 years (M = 10.75 yrs., SD = .80 yrs.). Students’ perceptions of autonomy support, satisfaction of basic psychological needs, sport and physical activity motivation and actual physical activity level were assessed. A quasi-experimental design was employed with two intervention groups (autonomy-supportive and controlling styles), as well as a control group. Results indicated that students in the autonomy-supportive condition demonstrated a significant increase in feelings of autonomy and increased their physical activity levels while demonstrating a significant decrease in extrinsic motivation over the course of the intervention. The results provide support for the expectation that well-designed and theoretically-based physical activity interventions can optimize learning and motivational outcomes for students in inclusive physical education settings.